Sex- and age-specific genetic analysis of chronic back pain. Issue 4 (April 2021) - Freidin, Maxim B.; Tsepilov, Yakov A.; Stanaway, Ian B.; Meng, Weihua; Hayward, Caroline; Smith, Blair H.; Khoury, Samar; Parisien, Marc; Bortsov, Andrey; Diatchenko, Luda; Børte, Sigrid; Winsvold, Bendik S.; et al.
Abstract : Abstract: Sex differences for chronic back pain (cBP) have been reported, with females usually exhibiting greater morbidity, severity, and poorer response to treatment. Genetic factors acting in an age-specific manner have been implicated but never comprehensively explored. We performed sex- and age-stratified genome-wide association study and single nucleotide polymorphism-by-sex interaction analysis for cBP defined as "Back pain for 3+ months" in 202, 077 males and 237, 754 females of European ancestry from UK Biobank. Two and 7 nonoverlapping genome-wide significant loci were identified for males and females, respectively. A male-specific locus on chromosome 10 near SPOCK2 gene was replicated in 4 independent cohorts. Four loci demonstrated single nucleotide polymorphism-by-sex interaction, although none of them were formally replicated. Single nucleotide polymorphism-explained heritability was higher in females (0.079 vs 0.067, P = 0.006). There was a high, although not complete, genetic correlation between the sexes ( r = 0.838 ± 0.041, different from 1 with P = 7.8E-05). Genetic correlation between the sexes for cBP decreased with age (0.858 ± 0.049 in younger people vs 0.544 ± 0.157 in older people; P = 4.3E-05). There was a stronger genetic correlation of cBP with self-reported diagnosis of intervertebral disk degeneration in males than in females (0.889 vs 0.638; P = 3.7E-06). Thus, the genetic component of cBP in the UK Biobank exhibits a mild sex- and age-dependency. This provides an insight into the possible causes of sex- and age-specificity in epidemiology and pathophysiology of cBP and chronic pain at other anatomical sites. Abstract : Supplemental Digital Content is Available in the Text.Genetic factors of chronic back pain exhibit mild sex- and age-specificity. This raises the need for sex- and age-stratified analyses of chronic pain in future studies.